Glossary of terms and concepts - Iglesias A.; López-Francos A.; Moneo M. (Drought management guidelines technical annex, 2007)
This glossary defines key concepts used in this document. These include the concepts of drought, water supply and demand, hydrology, risk, institutions and stakeholders as well as terms related to data, indicators and indices.